Legitimasi Publik Dan Tuntutan Pemakzulan Kepala Daerah Dalam Ketatanegaraan Perspektif Siyasah Dusturiyah - Pratama, Dhendy Setiawan; Khalid, Khalid (Lex Stricta : Jurnal Ilmu Hukum, 2025)
The impeachment of regional heads is a very important constitutional instrument in the Indonesian state administration, which aims to ensure the accountability and integrity of public officials at the local level. In the framework of a democracy based on direct elections, regional heads gain legitimacy through a mandate from the people, but this legitimacy is not absolute. With political and legal developments, various demands for impeachment have arisen, not only based on legal violations but also due to factors such as the weakening of public legitimacy. In practice, the impeachment process is often caught between legal norms and political realities, resulting in a process that is fraught with political nuances and power interests. This article attempts to analyze this phenomenon from two perspectives, namely constitutional law in Indonesia and fiqh siyasah, particularly siyasah dusturiyah as explained by Imam al-Mawardi in his work al-Ahkam al-Sultaniyyah. Through a normative legal research approach that refers to legislation and conceptual regulations, this article shows that the impeachment mechanism in Indonesia is clearly regulated in terms of norms, but in practice it often deviates from these norms. From a siyasah dusturiyah perspective, impeachment is defined as part of the mechanism for overseeing leaders who have lost the trust of the people or violated the principles of sharia and justice. Therefore, it is important to have synergy between applicable positive law and the principles of fiqh siyasah in order to create legitimate and accountable regional government management.